Effects of substituents on the photosensitizing and electrocatalytic properties of phthalocyanines - Maree, Suzanne Elizabeth (Rhodes University, Faculty of Science, Department of Chemistry, 2002)
In this work a selection of octasubstituted phthalocyaninato Zinc, Ge(IV) and Sn(IV) complexes were synthesized for possible use in photodynamic therapy and their photochemistry, photophysics and electrochemistry studied. Third-generation complexes containing steroids, e.g. cholesterol and estrone, were synthesized to improve tumour selectivity. The zinc phthalocyanine complexes (ZnPc) showed that complexes containing electron-donating groups have higher photostability. Germanium phthalocyanine complexes (GePc) undergo phototransformation rather than direct photobleaching and the tin phthalocyanine complexes (SnPc) undergo photobleaching mediated by photoreduction of the phthalocyanine ring. Singlet oxygen production showed increased in the following order: GePc>SnPc>ZnPc. Triplet lifetimes of the GePc (168-340Î¼s) are very similar to that of the ZnPc (197 - 366Î¼s), but the triplet lifetimes of the SnPc are ten fold shorter (10 - 32Î¼s ). Triplet quantum yields are higher for the GePc (0.20 - 0.50) and SnPc (0.08 - 0.45) than for the ZnPc (0.02 - 0.25). Fluorescence lifetimes of GePc ( 4.0 - 5.1 ns) are significantly longer than that of ZnPc (1.9 - 3.0 ns) and SnPc (0.2 - 0.4 ns). Fluorescence quantum yields decrease in the following order: GePc(0.21-0.31)>ZnPc(0.02-0.21)>SnPc(0.02- 0.06). Ring-substituted cobalt phthalocyanine complexes of the form CoPc(R)4 (R= NH2, N02, C(CH3)3, S03H and COOH) are compared for their catalytic activities towards the oxidation of cysteine. The potential for the electrocatalytic oxidation of cysteine is closely related to the Com/Co11 couple of the CoPc(R)4 complexes in acidic media and to the Con/Co1 couple in basic media. The catalytic current and the oxidation potential for cysteine are dependent on the pH of the solution, the potential becoming less positive and the currents increasing with increase in pH.
Keywords: Phthalocyanines